The outlook of land consolidation in Poland: Stakeholders`dilemmas and policy weaknesses - Markuszewska, Iwona (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
This paper discusses the issue of farmland merging in Poland in the face of social unwillingness and a poor legal policy. The theoretical consideration was carried out on the basis of the scientific body of literature, supported by empirical examples of farmland consolidation. The intention of the work is to present a comprehensive overview of land consolidation, where special attention was paid to the unsuccessful merging efforts. As a result of the investigation, attempts were made to answer the following question: Is land consolidation necessary to improve the condition of Polish farming?
Keywords: farmland merging; stakeholders; policy; Poland